Development of ε-poly(L-lysine) carbon dots-modified magnetic nanoparticles and their applications as novel antibacterial agents - Jiang, Yuying; Xu, Xinkai; Lu, Jinglin; Yin, Chuqiang; Li, Guotai; Bai, Longjian; Zhang, Tiantian; Mo, Jianning; Wang, Xiaoyu; Shi, Qiang; Wang, Ting; Zhou, Qihui (Frontiers in Chemistry, 2023)
Magnetic nanoparticles (MNPs) are widely applied in antibacterial therapy owing to their distinct nanoscale structure, intrinsic peroxidase-like activities, and magnetic behavior. However, some deficiencies, such as the tendency to aggregate in water, unsatisfactory biocompatibility, and limited antibacterial effect, hindered their further clinical applications. Surface modification of MNPs is one of the main strategies to improve their (bio)physicochemical properties and enhance biological functions. Herein, antibacterial ε-poly (L-lysine) carbon dots (PL-CDs) modified MNPs (CMNPs) were synthesized to investigate their performance in eliminating pathogenic bacteria. It was found that the PL-CDs were successfully loaded on the surface of MNPs by detecting their morphology, surface charges, functional groups, and other physicochemical properties. The positively charged CMNPs show superparamagnetic properties and are well dispersed in water. Furthermore, bacterial experiments indicate that the CMNPs exhibited highly effective antimicrobial properties against Staphylococcus aureus. Notably, the in vitro cellular assays show that CMNPs have favorable cytocompatibility. Thus, CMNPs acting as novel smart nanomaterials could offer great potential for the clinical treatment of bacterial infections.